Compatibility of the Capital of Nusantara’s Form of Government Against Article 18B Section (1) of the 1945 Constitution of the Republic of Indonesia - Hantoro, Bimo Fajar (SASI, 2022)
Introduction: With the promulgation of Law Number 3 of 2022 on State Capital, the government realized its plan to relocate the nation’s capital from the Specific Capital Region of Jakarta to the Capital of Nusantara on the Kalimantan Island. However, the law's passage has sparked a debate directed at the Indonesian new capital's form of government which is deemed to violate the 1945 Constitution of the Republic of Indonesia, specifically Articles 18, 18A, and 18B.Purposes of the Research: The purpose of this study is to examine and analyze the compatibility of the Capital of Nusantara’s form of government against Article 18B section (1) of the 1945 Constitution of the Republic of Indonesia.Methods of the Research: This is a normative juridical study using primary and secondary legal materials that are relevant to the topic of this study.Results of the Research: The results showed that the specific arrangements of the Capital of Nusantara’s form of government are normatively compatible with Article 18B section (1) of the 1945 Constitution of the Republic of Indonesia for two reasons, namely: the position between Article 18B section (1) and Article 18 as equals and that both of them apply independently; and the specificity that can be regulated for the Capital of Nusantara is flexible which means that the extent of the specificities can be so broad, including in terms of the form of government.